Distinct Modulations of Northwest Pacific Tropical Cyclone Precipitation by Atlantic Multidecadal Oscillation and Interdecadal Pacific Oscillation - Jiuwei Zhao; Ruifen Zhan; Daehyun Kim; Jong‐Seong Kug; Jingchao Long; Leying Zhang; Xiaofan Ma (Geophysical Research Letters)
Abstract The interdecadal variability of tropical cyclone precipitation (TCP) over the western North Pacific (WNP) has not been thoroughly explored in previous studies. Here, we show that the TCP variations are modulated by both the Atlantic Multidecadal Oscillation (AMO) and Interdecadal Pacific Oscillation (IPO) as evidenced by reanalysis data and model experiments. A clustering analysis of tropical cyclone tracks shows that the AMO dominates a dipole pattern of TCP anomalies in the South China Sea and along the coastal eastern China. Meanwhile, the IPO dominates TCP over the southeastern WNP. Further analyses show that the AMO, particularly its extratropical component, affects TCP over the WNP by triggering an eastward‐propagating Rossby‐wave train, resulting in a pair of anomalous gyres over the WNP. Contrastly, the IPO modulates TCP by stimulating tropical circulation anomalies via the tropical pathway. These findings shed light on improving near‐term TCP forecast and its regional influence on East Asia.